UTILIZATION OF THE ACTIVITIY BASED COSTING (ABC) SYSTEM IN DETERMINING OVERCOSTING OR UNDERCOSTING TUITION FEES - Maksum, Asep (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This study aims to identify the application of the Activity Based Costing (ABC) system in Private Universities in determining the cost of goods for the study program. The main focus of this study is to identify the activities of primary and secondary study programs to determine cost drivers and determine the rates of each of these activities. The research method through case studies by conducting quantitative descriptive analysis is collecting data, compiling data, classifying data and deciphering data. The source of the data came from interviews and observation of financial statement documents with samples at XYZ University. The calculation results obtained the conclusion that several social and economic study programs at XYZ University were in over costing and some exact study programs were under costing conditions. The implications of the results of this study provide input for XYZ University in developing an Activity Based Management (ABM) system as a process of continuous improvement in improving the quality of education.